Open Access and the New Challenges for a Global World - Alla Guzhva (027.7)
Open access is known as a valuable initiative for science communication per excellence. This publication draws attention to the critical role of open-access documents in higher education in Ukraine. On the other hand, I demonstrate that people 19–20 years old (students-interns at American University Kyiv) choose open access sources for their academic aims. This fact reaffirms the significance of the Budapest Open Access Initiative as an enabler of modern education.